Public records and archives in classical Athens - Sickinger, James P. (Studies in the history of Greece and Rome., 1999)
Sickinger (classics, Florida State University) explores the use and preservation of public records, especially laws and decrees, in the ancient Athenian democracy of the archaic and classical periods. He demonstrates that inscriptions on marble represented only a small part of Athenian record keeping, and traces the development of more numerous and more widely used archival texts written on wooden tablets or papyri, from their first use to record laws in Drakon and Solon in the late seventh and early sixth century BC, through the proliferation of public record keeping of all sorts that occurred over the course of the sixth and fifth centuries.